(untitled) (PERcursos Linguísticos, 2020)
Regarding legal discourse, the argumentative work is the sine qua non condition in order to make the potential interlocutors (author and defendant) achieve the goals they have proposed. Thus, each participant of an interaction expresses a self and the other evaluation whose construction is stablished in the communicative event in which it is inserted, what leads to the Face Elaboration Theory (GOFFMAN, 1980, 2011). Associated to the face preservation’s idea, Brown and Levinson (1987 [1978]) present the theory of Politeness, in which shows acts that threaten the interlocutors faces. In legal texts, which the communicative process concerns the fight for an alleged right, it is indispensable that the interlocutors are capable to build an argumentation. Based on this premise, this article aims at showing how the pragmatic principles of Acts of Speech, (AUSTIN, 1990 [1962]), Face, (GOFFMAN, 1980, 2011) and Politeness, (BROWN and LEVINSON, 1987 [1978]) are essential for the construction of an argumentative speech.